The role of leaf area and photosynthesis in optimising the sowing date of maize - Bene, Enikő; Sárvári, Mihály (Acta Agraria Debreceniensis, 2015)
Our sowing date experiment took place in the Demonstration Garden of Institution of Plant Sciences, Agricultural Center of University of Debrecen, in 2012–2014. The thesis contains data of test year 2014. Our purpose, besides several other examinations, was to observe how sowing date influences leaf area index and activity of photosynthesis of maize hybrids, and how those factors affect fruiting. In the experiment we monitored the change of the leaf area index and the photosynthesis of hybrids with four different growing seasons. Based on the results, it can be concluded that most of the examined hybrids reached their smallest leaf area with the third sowing date and with the highest yield results. Hybrid Da Sonka had the largest leaf area (4.10 m2 m-2), and hybrid DKC 4590 produced the highest yield (13.16 t ha-1) with the third sowing date. During testing the photosynthetic capacity, the extremely high performance of the youngest plants with the third sowing date is outstanding, which can be explained by the different ripening periods. Examination of the correlation between the photosynthetic capacity and the yield, by linear regression analysis, also proves that photosynthesis has a determinative role in fruiting. The results obtained confirm that not only the environmental and agricultural factors in the growing season have effect on the yield, but also other factors like the leaf area index and the photosynthesis are determinative parameters, and all those factors together, modifying effects of each other, develop average yields.